2005
DOI: 10.1016/j.jtcvs.2004.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Immunophilin ligands FK506 and cyclosporine A improve neurologic and histopathologic outcome after transient spinal cord ischemia in rabbits

Abstract: FK506 and chronic administration of cyclosporine A, but not rapamycin, protect the spinal cord from transient ischemia. Although these results are compatible with inhibition of calcineurin in the mechanism of neuroprotective action of these drugs, other effects through different pathways cannot be excluded before further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Our data indicate the existence of cross talk between the action of 0.25 -1 µM CsA as well as 1 µM FK506 on cPLA 2 and CaN in anti-apoptotic signal transduction pathways. Moreover, we have shown that immunophilin ligands at these concentrations protected glial cells against ischemia-induced apoptosis, as evidenced by the increase of cell viability, mitochondrial function restoration, and attenuation of oxidative stress.…”
Section: +mentioning
confidence: 64%
“…Our data indicate the existence of cross talk between the action of 0.25 -1 µM CsA as well as 1 µM FK506 on cPLA 2 and CaN in anti-apoptotic signal transduction pathways. Moreover, we have shown that immunophilin ligands at these concentrations protected glial cells against ischemia-induced apoptosis, as evidenced by the increase of cell viability, mitochondrial function restoration, and attenuation of oxidative stress.…”
Section: +mentioning
confidence: 64%
“…Recently, it has been reported that both FK506 and CsA are effective in reducing injury in rabbit spinal cord ischemia/ reperfusion models. This suggests that in neural tissue the calcineurin-inhibiting property of CsA is the protective mechanism [19]. …”
Section: Commentmentioning
confidence: 99%
“…Binding of FK506 to FKBP12 led to forming a complex, which inhibits calcineurin (Liu et al 1991); this in turn, would be expected to increase the amount of the active form of the growthassociated protein GAP-43 in neurons (Bavetta et al 1999). In relevant studies were shown, that FK506 offered neuroprotection following brain and spinal cord ischemia (Benetoli et al 2007;Furuichi et al 2003;Tachibana et al 2005;Tokime et al 1996;Yagita et al 1996), traumatic brain (Marmarou and Povlishock 2006;Reeves et al 2007), and spinal cord injury (Lopez-Vales et al 2006;Madsen et al 1998;Nottingham et al 2002;Voda et al 2005Voda et al , 2007. However, FK506 effectiveness varied depending on model of CNS injury and FK506 regimen.…”
Section: Introductionmentioning
confidence: 99%